The evaluation of the static and dynamic balance disorders in patients with psoriatic arthritis - ŞANAL TOPRAK, CANAN; ATAGÜNDÜZ, MEHMET PAMİR; DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2018)
To evaluate the static and dynamic balances in psoriatic arthritis (PsA) and to investigate their relationship with clinical and functional parameters. Patients diagnosed with PsA and healthy controls were recruited consecutively into the study. The demographic variables such as age, sex, body mass index of the subjects were noted. Radiographic images were examined for the detection of foot deformities. Foot and Ankle Outcome Score' (FAOS) was used to assess foot function. The dynamic and static balance of the patients was evaluated by Berg Balance Scale' (BBS) and Neurocom Balance Master' device. The fatigue (Multidimensional Assessment of Fatigue: MAF), depression (Beck Depression Inventory: BDI) and sleep disorders (Pittsburgh Sleep Quality Index: PSQI) of all patients were evaluated. This study included 50 PsA patients and 50 healthy controls with mean ages of 45.02 (SD 12.81) and 45.12 (SD 10.56), respectively. Demographic data of both groups were similar. Concerning the balance tests, there were significant differences (p<0.05) between patient and control groups about the all tests of sway velocity (except on foam surface eyes closed test), end sway of tandem walk test, movement time of bilateral step up over test and lift up index of left step up over test. There was no significant correlation between static and dynamic balance parameters with MAF, BDI, PSQI, foot deformities and FAOS. The static and dynamic balance impairments are seen in PsA. As the balance parameters had no significant correlation with functional and clinical data, they are acceptable as independent parameters during the course of the disease.
Keywords: Psoriatic arthritis; Balance; Foot; DISEASE-ACTIVITY; TURKISH VERSION; FOOT; RELIABILITY; MANAGEMENT; STABILITY; VALIDITY; BURDEN; FALLS